2021
DOI: 10.1002/brb3.2419
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among self‐injury, experiential avoidance, cognitive fusion, anxiety, and depression in Chinese adolescent patients with nonsuicidal self‐injury

Abstract: Objective: To explore relationship among self-injury behavior, experiential avoidance, cognitive fusion, anxiety, and depression in Chinese adolescent patients with nonsuicidal self-injury (NSSI). Methods: Cognitive fusion questionnaire (CFQ), Acceptance and Action Questionnaire-2nd edition (AAQ-II), adolescent nonsuicidal self-injury behavior questionnaire (ANSAQ), Hamilton Anxiety Scale (HAMA), and Hamilton Depression Scale (HAMD) were used as research tools to investigate 120 subjects with NSSI and 130 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
2
18
0
2
Order By: Relevance
“…The results showed that the NSSI group had significantly higher scores in childhood trauma, alexithymia, depression, and anxiety than the non-NSSI group. Several studies have also found a strong association between NSSI and childhood trauma, alexithymia, depression, and anxiety (Groschwitz et al, 2015;Hu et al, 2021;Norman & Borrill, 2015;Thomassin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the NSSI group had significantly higher scores in childhood trauma, alexithymia, depression, and anxiety than the non-NSSI group. Several studies have also found a strong association between NSSI and childhood trauma, alexithymia, depression, and anxiety (Groschwitz et al, 2015;Hu et al, 2021;Norman & Borrill, 2015;Thomassin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with the theory of acceptance commitment therapy. 44 The theory suggests that anxiety and NSSI may be rooted in psychological inflexibility, such as experiential avoidance and cognitive integration. Individuals attribute cognitive fusion to some of their own mistakes, and their behavior is limited by their own negative emotions; experiential avoidance implies that individuals achieve escape from negative emotions and negative events through NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…The total scores range from 7 to 49, with the higher scores indicating greater psychological inflexibility. CFQ-F was used to measure cognitive fusion using a 9-items self-reported questionnaire with a 7-point scale ( 32 ). The total scores range from 9 to 63, with the higher scores indicating higher psychological inflexibility.…”
Section: Methodsmentioning
confidence: 99%